Representaciones del cáncer de cuello uterino y su relación con la sexualidad femenina Las voces de los actores políticos y de la sociedad civil de Ayacucho, Lima, Piura y Ucayali en el marco de la introducción de una nueva vacuna - Cristobal, Irene (2007)
The uterin cancer is the second cause to death by neoplasia in Peruvian women. In the context of the recent introduction of a vaccine against this kind of cancer, this document is presented to show the picture of uterin cancer and its relation with the leaders and political actors’s sexuality picture as a setting to promote or not the introduction of this vaccine as a health politic. The document picks the voices of political actors and members of civil society from Ayacucho, Lima, Piura and Ucayali.